Sustainable Transport Assessment through Passenger Density and Operational Headway - Sumasto, Fredy; Gurning, Ridho Hans; Pratama, Indra Rizki; Arohman, Abdul Wahid; Purbaningrum, Sanurya Putri (Institut Transportasi dan Logistik Trisakti, 2025)
This study investigates the operational performance and sustainability of two urban minibus routes D41 (Gandaria–Cibinong) and D37 (Cibinong–Kampung Rambutan) in the Depok–Bogor region of Indonesia. Using field observations and GPS-assisted time tracking, three indicators were analyzed: passenger load factor, operational headway, and travel time. Results show that while both routes exceeded the government’s 70% load factor benchmark during peak hours, performance dropped below 50% at midday. Headway generally remained within the acceptable range of 2–5 minutes, but D37 exhibited the shortest intervals during morning peaks. D37 also experienced prolonged travel times, often exceeding 80 minutes. These findings highlight the inefficiencies of informal public transport systems, particularly their inability to scale services to match fluctuating demand. This study proposes a low-cost, data-driven framework for assessing route efficiency and supports the integration of informal routes into broader transport planning. The results are relevant to urban mobility reform in developing cities.